Implementasi Peraturan Pemerintah Tentang Pelaksanaan Perceraian Bagi PNS PP No. 10 TAHUN 1983 jo. PP NO. 45 Tahun 1990 (Studi Kasus di Pengadilan Agama Surakarta) - Rahmania, Nur Farikha; , Mutimatun Ni'ami, S.H., M.Hum (2016)
The purpose of this paper is to examine the effectiveness of the implementation of divorce civil servants in Government Regulation Number 10 of 1983 jo. Government Regulation Number 45 of 1990. This research is descriptive method that describes the state of the object to be examined. Data relating to the issues to be discussed, taken from Surakarta Religious of Courts. Data collection methods used are the source of primary data and secondary data sources. Sources of primary data in the form of literature and secondary data sources such as interviews. Data analysis method used is normative (doctrinal), conceived as a legal norms made in writing and in legislated by the institution or the authorities.